2018
DOI: 10.1002/cyto.b.21729
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Reference Values of MDR‐ABC Transporter Activities in CD3+ Lymphocytes of Healthy Volunteers Using a Flow Cytometry Based Method

Abstract: Background: MDR transporters are important biomarkers of drug resistance in cancer and in autoimmune conditions. We determined the MDR1, MRP1 and BCRP activity in CD3+ lymphocytes using a flow cytometry based method from 120 healthy volunteers in order to describe normal reference values of the activity of these transporters. The effects of gender and age were also determined.Methods: The Solvo MDQ Kit™ was used for measurements. In this assay, fluorescent reporter substrates (Calcein-AM for MDR1 and MRP1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Apply sequential gating strategy for the analysis (an example is provided in ref. ). Within the desired cell subset gate, determine the corresponding geo‐MFI values of the reporter substrate applied.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Apply sequential gating strategy for the analysis (an example is provided in ref. ). Within the desired cell subset gate, determine the corresponding geo‐MFI values of the reporter substrate applied.…”
Section: Discussionmentioning
confidence: 97%
“…In case of hematological malignancies, the MAF C values in tumor cell populations are usually found between 0 and 50, but in extreme cases, values can be as high as 70. Reference values of MAF values in CD3 + lymphocytes were determined in a healthy population of 120 individuals . Importantly, MAF values are independent from gender.…”
Section: Discussionmentioning
confidence: 99%
“…At later time points, MAF C values above 20.3 and MAF MRP1 above 6.0 and MAF MDR1 values above 13.9 in CD3 + cells also predict unfavourable treatment response. Of note, these cut-off values are all below the respective reference ranges in healthy individuals established in our earlier study [3]. Conclusion: Importantly, little is known about the relation of MDR activities and therapeutic success to bDMARDs.…”
Section: Referencesmentioning
confidence: 45%
“…Studies in healthy individuals and participants with rheumatologic disease or lung transplant evaluated P-gp function using only a single timepoint which limits the ability to detect pharmacodynamic differences over time from these data. 10,[24][25][26][27] Although past investigations have reported mixed outcomes while studying P-gp expression and sex, 15,16,18,19 our study observed that White male and female KTRs exhibited greater P-gp function in PBMCs at time 0 h and with the composite parameter, AUC 0-12h % ΔMFI, compared to Black men and women. 12,25 The pair-wise comparison for each significant P-gp parameter was noted between White and Black women which reinforces the combined race-sex association.…”
Section: Comparison Of Timepoints Within the Same Dosing Interval And...mentioning
confidence: 63%
“…11,20,21 Further investigations are needed to examine race and sex differences in P-gp function in PBMCs and lymphocyte subpopulations in stable transplant recipients and healthy participants as well as the application of this research blood tests as a routine liquid biopsy to guide drug therapy adjustments post-transplant. 12,25,26 Recently, liquid biopsies have been utilized to quantify proteins, such as P-gp, and efforts have been made to correlate such expression to activity (e.g., function) with patient response. Liquid biopsies have successfully detected variability in P-gp expression, and expression has been moderately and strongly correlated to P-gp activity.…”
Section: Comparison Of Timepoints Within the Same Dosing Interval And...mentioning
confidence: 99%